Henry of Ghent’s posittion in the controversy concerning the real difference of essence and existence in created beings - Surzyn, Jacek (Folia Philosophica, 2001)
The article is devoted to the presentation of the position of Henry of Ghent in the controversy concerning the real difference between essence and existence. Henry was the first to strongly oppose Gilles of Rome's thesis that essence and existence really differ by way of things - inter rem et rem. Henry's position was based on assuming a different solution. He claimed that in the case of essence and existence we do not deal with the real difference or with mental difference, but with a specific type of difference as a relation to something third. For if we state that something exists we indicate that is has a cause, that it is causal. Hence existence is intentionally different from essence, i.e. it points to the cause of a given being which is the cause of its such and not other essence. Henry's idea of difference played an important role in the subsequent development of the controversy.